2016
DOI: 10.1007/s11255-016-1286-z
|View full text |Cite
|
Sign up to set email alerts
|

The application of CT voiding urethrography in the evaluation of urethral stricture associated with fistula: a preliminary report

Abstract: CT voiding urethrography is a useful technique for the diagnosis of urethral disease, especially in male patients suffering from urethral stricture associated with fistula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…A CT voiding urethrography can provide useful information in case of stricture related fistulas [18].…”
Section: Symptoms and Diagnosismentioning
confidence: 99%
“…A CT voiding urethrography can provide useful information in case of stricture related fistulas [18].…”
Section: Symptoms and Diagnosismentioning
confidence: 99%
“…Some studies report the usefulness of CT-VCUG for evaluating the bladder and posterior urethra [5,9,10]. Chou et al [9] in a study of 13 males with traumatic antecedents reported the diagnostic potential of 3D CT-VCUG after intravenous (i.v.)…”
Section: Discussionmentioning
confidence: 99%
“…Su et al [10] described 3D and 4D CT-VCUG after i.v. the contrast in 70 healthy subjects (43 males and 27 females) using 640-slice dynamic volume CT. Two studies using CT-VCUG [5,9] took a mean time of 8.8 and 9 min (range, 4-20 min) and another performing combined retrograde and voiding CT [11] took a mean time of 10 min (range, 6-20 min). The mean time for CT-RUG in our study was 6.1 min (range, 4.7-7.7 min) and it must be remembered that a lot of this time was spent by the nurse performing the clamp method because the CT technique and cystourethral filling with contrast were quick.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the urinary bladder and proximal urethra, such structural defects recognizable using a combination of retrograde urethrogram and voiding cysto-urethrogram include irregular inner bladder margin suggestive of thickened urinary bladder wall (detrusor hypertrophy) with implication similar to that of observing trabeculation and sacculation at cystoscopy [8], dilated proximal urethral segment and overdistended urinary bladder with significant postvoid residual urine volume [6]. Others include urinary bladder diverticulum of any size which could be solitary or multiple, vesico-ureteric reflux of any grade which could be unilateral or bilateral, and urethrocutaneous fistula of any course which could be solitary or multiple (watering-can perineum) [2, 9]. All of these are demonstrable with a combination of retrograde urethrogram and voiding cysto-urethrogram.…”
Section: Introductionmentioning
confidence: 99%